1988
DOI: 10.1007/bf00247575
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve grafts lacking viable Schwann cells fail to support central nervous system axonal regeneration

Abstract: Peripheral nerve grafts were implanted bilaterally into the diencephalon of adult hamsters. One graft segment contained both viable Schwann cells and their basal lamina tubes. The Schwann cell population in the second graft segment was killed by freezing prior to implantation. Seven weeks after graft implantations, the extracranial end of each graft segment was exposed, transected and labelled with a fluorescent tracer substance. One week after the labelling procedure each animal was perfused and the diencepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 29 publications
1
43
0
2
Order By: Relevance
“…Modern axon-tracing technologies confirmed both that CNS axons regrow into peripheral nerve grafts (84,85), and that this regrowth is critically dependent on neurotrophic factors produced by live cells in grafts (86,87). Freezing nerves and killing resident cells prevented CNS axon growth into them, and injection of nerve growth factor (NGF) into frozen grafts restored their ability to attract regeneration of NGF-sensitive CNS axons, showing that permissive matrix alone is not sufficient for regrowth (86,87). Numerous subsequent studies show that delivery into SCI lesions of developmentally active neurotrophins such as brain-derived neurotrophic factor axon regeneration through SCI lesions (41).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
See 1 more Smart Citation
“…Modern axon-tracing technologies confirmed both that CNS axons regrow into peripheral nerve grafts (84,85), and that this regrowth is critically dependent on neurotrophic factors produced by live cells in grafts (86,87). Freezing nerves and killing resident cells prevented CNS axon growth into them, and injection of nerve growth factor (NGF) into frozen grafts restored their ability to attract regeneration of NGF-sensitive CNS axons, showing that permissive matrix alone is not sufficient for regrowth (86,87). Numerous subsequent studies show that delivery into SCI lesions of developmentally active neurotrophins such as brain-derived neurotrophic factor axon regeneration through SCI lesions (41).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
“…Based on these observations, Cajal theorized that in contrast with developing CNS and injured peripheral nerves, the injured adult CNS lacked diffusible chemoattractants required to promote axon regrowth. Modern axon-tracing technologies confirmed both that CNS axons regrow into peripheral nerve grafts (84,85), and that this regrowth is critically dependent on neurotrophic factors produced by live cells in grafts (86,87). Freezing nerves and killing resident cells prevented CNS axon growth into them, and injection of nerve growth factor (NGF) into frozen grafts restored their ability to attract regeneration of NGF-sensitive CNS axons, showing that permissive matrix alone is not sufficient for regrowth (86,87).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
“…Messenger RNA data indicates that levels of NGF and GDNF, but not BDNF or NT3, are elevated in PNGs at 10 days and 20 days after grafting when comparing levels in the PNG to adjacent spinal cord tissue [33]. Acellular grafts (resulting from a freeze-thaw procedure to kill Schwann cells and fibroblasts) were found to be far less effective in supporting axonal growth, despite the presence of laminin coated Bands of Büngner [9,34,35]. Another advantage with using a PNG over other neural tissues for transplantation is that Schwann cells enthusiastically form myelin sheaths around many/most of the axons within the PNG, bestowing on these regenerated fibers the ability to efficiently conduct action potentials at or near rates observed for intact spinal cord axons [36,37].…”
Section: Technical Considerations For Using a Peripheral Nerve Graftmentioning
confidence: 99%
“…Moreover, their abilities to organize into PN-like aligned arrays (Montgomery and Robson, 1993) and to modify the lesion-induced, dense astrocytosis may promote axonal regeneration. In fact, Schwann cell-free PN grafts fail to support CNS regeneration (Berry et al, 1988;Smith and Stevenson, 1988) as do Schwann cell-free collagen membranes (Kromer and Cornbrooks, 1985;Paino et al, 1994). A number of implantation studies have demonstrated that Schwann cells represent a very suitable and eective substrate for stimulating axonal regeneration Martin et al, 1991;Montero-Menei et al, 1992;Neuberger et al, 1992;Montgomery and Robson, 1993;Raisman et al, 1993;Brook et al, 1994;Paino et al, 1994;Harvey et al, 1995;Plant et al, 1995;Xu et al, 1995b;Chen et al, 1996).…”
Section: Peripheral Nerve/schwann Cellsmentioning
confidence: 99%